基于变传动比函数的非圆齿轮设计方法与分析 - 孙科; 郑方焱; 童婷; 陈定方 (Jixie chuandong)
Based on the variable ratio function,by using the geometric model of pinion cutter,the simple algorithm of tooth profile of effectively solved non-circular gear is proposed.Based on the given variable ratio funct ion,the equation of non-circular gear pitch curve is derived.The equation of tooth profile is determined by the processing principle of slotting gear,and the numerical algorithm and Pro/ E modeling is used to get three-dimensional model of non-circular gear.Meanwhile,based on dynamics simulation software ADAMS,the simulation of gear teeth meshing is analyzed.By means of calculat ions on some examples,it proves the correctness,conciseness,generality and innovat ion of the algorithm.